Activity time budgets of ecologically relaxed groups of geladas (Theropithecus gelada) and mandrills (Mandrillus sphinx): what happens when time is no longer a constraint?. Issue 4 (4th July 2022) - Ortega-Ballesteros, Leticia; Amezcua-Valmala, Nerea; Mera-Cordero, Sheila; Hernández-Lloreda, María V.; Colmenares, Fernando
Abstract : Primates spend their daytime engaged in four non-overlapping, time-consuming, biologically relevant activities, namely, feeding, moving, resting, and socializing. The present study addressed two issues relevant to socio-ecological theory and life-history theory: how do individuals re-schedule the time allocated to these activity categories when they live in ecologically relaxed settings, where they are food-provisioned, live under benign weather conditions, and are predator-free? How do individuals trade the different activity categories against each other in a relatively time constraint-free setting? We predicted that feeding and moving times should decrease and resting and socializing times should increase. We also explored the relation of feeding time to resting time and social time to see which activity category is more dispensable when feeding time increases. Here we analyzed the activity time budgets of a group of geladas, Theropithecus gelada, and a group of mandrills, Mandrillus sphinx, housed in captivity in similarly vegetated and large-sized enclosures, and exposed to identical temperate-zone climate conditions, and compared them to time budget data available for wild groups of geladas and baboons. We found that they displayed activity budgets that largely matched those reported for wild groups of geladas and baboons, except moving time that decreased, but in geladas solely. We also found a tighter negative relation of feeding to resting time than to social time. These findings indicate that freeing individuals in a captive setting from the time constraints and pressing demands faced by their wild counterparts does not necessarily cause a significant re-scheduling of their activity time budgets. They also support the "social glue" hypothesis, as an increase of feeding time is associated with a significant decrease in resting, not social, time. The notion of a captivity-typical versus wild-typical profile of activity time budgets appears unsupported given the remarkable overlapping of time budget scores across settings and the huge inter-populational, intergroup, and intragroup variation reported.